HEGEMONI CERPEN WAJAH ITU MEMBAYANG DI PIRING BUBUR KARYA INDRA TRANGGONO: ANALISIS WACANA KRITIS - Nelda Sari Siregar; Else Liliani (Center of Language and Cultural Studies, 2019)
The purpose of the study was to describe the dimensions of the text, the practice of discourse, socio-cultural practices, and the ideological formations in the short stories that face imagined on porridge plates. The theory used is the theory of sociology of Gramsci hegemony. The method used is a qualitative method with the Fairclough model of critical discourse analysis techniques. The results of the study are a form of hegemony when traditional markets turn into modern markets and make people have a consumptive lifestyle. The author expresses his criticism of the current phenomenon subtly with the symbol of genderuwo which has greed and hegemonic character. Genderuwo is represented as a capitalist system which is currently controlling society. The form of ideological formation in the form of authoritarianism-capitalism and humanistic-mysticism. There are groups of hegemony, pro-hegemony, and groups of counter-hegemony. The hegemony group is the main actor in the occurrence of hegemony (the dominant group), while the pro-hegemony group is a figure who supports the occurrence of hegemony, the counter-hegemony group consists of people who oppose the occurrence of hegemony (cultural rise).